Evaluate the effectiveness of skills to send and beating the overwhelming according to the analytical program using the computer in volleyball - Alwan, Bahera; Abedulhamid, Manahel; Ali, Tariq (Journal of Physical Education, 2015)
The aim of this research was to evaluate the effectiveness spick and serve skills performance skills according to a computer-based analytical of Iraqi volleyball team players which participating in the Arab Volleyball Championship that held in Bahrain for the period from 4/11/012 to 11/14/2012. 1. The objectives of the research was to design a program to analysis spick and serve skills performance. 2. Analysis the effectiveness of skills performance of Iraqi national team. The researcher used analysis program adopted by the International Federation of Volleyball after it was adapted to suit the aims of the research by modifying program interfaces for the purpose of evaluation of skills, especially spick skill from areas 2&4 and the player in position 3 and after agreement with staff training in order to develop the level of performance of the players and point out the positive and negative aspects in team performance to overcome the negatives and enhance the positive aspects